Synthesis and Physico-Chemical Properties of Oligomeric Inhibitors of Corrosion on the Base of Nitrogen, Phosphorous-Containing Compounds - Akbarov Kh.I., Eshmamatova N.B., Fayzullaev N.I., Kalyadin V.G., Azimov L.A. (International Journal of Advanced Science and Technology, 2020)
In article the results of electrochemical and gravimetrical investigations by the influence of new elaborated oligomeric salts on the base of some organic compounds on the corrosion behavior of steel samples (St –3) in different mediums are presented. It was shown that protective effect of investigated oligomeric salts has been increased with increasing their molecular mass and hydrocarbon radicals, diminutions presented in the molecules. The influence of the experiments duration and also some other factors on the protective effect of the investigated oligomers have been discussed. Keywords: inhibitors, steel corrosion, mechanism of inhibition, urea, phosphate urea, phosphate of dimethilolurea, dimethilolhexamethylendiamine, dimethilolmelamin, oligomeric, chronopotentiometry, rentgenophloren cencehetero atom, adsorption, polarization curves, polarization resistance, hydropholical, synergism, electro-donoral, IKM, OIKM.